Barium lines in high-quality spectra of two metal-poor giants in the Galactic halo - Cescutti, Gabriele; Morossi, C.; Franchini, M.; Marcantonio, P. Di; Chiappini, C.; Steffen, M.; Valentini, M.; François, P.; Christlieb, Norbert; Cortés, C.; Kobayashi, C.; Depagne, E. (Astronomy and astrophysics, 2021)
Context. Theoretical results showed the possibility that neutron capture elements were produced in the early Universe by two different sources: a frequent s-process source hosted by rotating massive stars, and a rare r-process source hosted most likely by neutron star mergers. The two sources produce barium with different isotopic compositions.Aims. We aim to investigate the lines of barium in two halo stars, HD 6268 and HD 4306. The spectra present an exquisite quality, both in terms of resolution (R > 100 000) and signal-to-noise (~400). Due to hyperfine splitting (hfs) effects, barium lines are expected to show slightly different profiles depending on the barium isotopic fraction.Methods. We applied a standard local thermodynamic equilibrium synthesis of the barium lines. We compared the synthetic results assuming an s-process isotopic pattern or an r-process isotopic pattern for the two barium lines for each star that exhibited hfs. We also applied a methodology, less dependent on the accuracy of the theoretical Ba hfs structure, that transforms the lines of HD 4306 into those we would observe if its atmospheric parameter values (i.e. Teff, log g, micro- and macro-turbulence, V sin i, and Ba abundance) were the same as those of HD 6268.Results. With both methods, our results show that the barium lines with hfs effects of HD 4306 are in agreement with an s-process composition and the lines in HD 6268 have a different profile, which is most likely linked to the presence of an r-process isotopic pattern.Conclusions. Two lines of barium of HD 6268 and HD 4306 seem to confirm the theoretical expectation that both r-process events and also s-process contribution by rotating massive stars have polluted the ancient halo of our Galaxy.
Gesehen am 09.02.2022